Evaluation of masseteric vestibular evoked myogenic potentials in paediatric population with normal vestibular function. - Kanık, Ayşenur; Baydan Aran, Mine (International Journal of Audiology, 2026)
Objective: This study aimed to evaluate the function of the otolith organ and vestibulo-trigeminal pathway using mVEMP testing in a paediatric population and to establish normative data for mVEMP testing in the paediatric population. Design: Participants with normal vestibular function and no additional disorders were further assessed using mVEMP evaluation. The mVEMP results were analysed and compared based on gender, ear side, and age group. Study Sample: Our study included 66 participants, divided into three age groups: group 1 (10–12 years, n = 22), group 2 (13–15 years, n = 22) and group 3 (16–18 years, n = 22). Results: P1 latencies at 100, 85 and 80 dB nHL were significantly shorter in females compared to males (p < 0.05). When comparing between ears, N1 latency at 100 dB nHL and N1-P1 inter-wave latency at 90 dB nHL were significantly shorter in the right ear compared to the left ear (p < 0.05). Additionally, a statistically significant difference was observed for N1-P1 amplitude at 100, 90, 85 and 80 dB nHL (p < 0.05). Conclusion: The findings of this study suggest that obtaining normative data for the mVEMP test in a paediatric population may be useful in the assessment of vestibulo-trigeminal pathways.